Influence of Work Motivation and Work Discipline on Employee Work Productivity at PT. Surya Setia Prosperity Hammer - Azwar A; Rajindra Rajindra; Mutmainnah Mutmainnah (International Journal of Health, Economics, and Social Sciences (IJHESS), 2021)
This study aims to obtain information about the influence of motivation and discipline on employee productivity at the Surya Setia Sejahtera Palu company. The researcher raises the problem, namely whether there is a significant simultaneous and partial effect on motivation and discipline variables on employee productivity. From the problems above, the researcher proposes a hypothesis that motivation and discipline variables have a significant effect on productivity. To prove this hypothesis, this study uses a descriptive causal method and multiple linear regression analysis techniques. The sampling technique is a probability sampling technique or simple random sampling, with a sample size of 75 respondents. The results of the hypothesis test in this researcher are known that both motivation and discipline variables simultaneously have a positive and significant effect on work productivity with a value of F 0.000 <0.05. Then the work motivation variable partially also has a positive effect on productivity with a significance value of 0.000 <0.05 and the work discipline variable partially also has a positive influence on work productivity with a significance value smaller than 0.002 < 0.05.